Infectious complications of prosthetic arteriovenous grafts for hemodialysis: prevention is better than cure. (May 2014) - Galanopoulos, Georgios; Lambidis, Constantinos
Abstract Synthetic arteriovenous grafts for hemodialysis constitute the second choice in comparison with native arteriovenous fistulas. Lower patency rates and significantly more frequent infections are the main disadvantages of hemodialysis grafts over fistulas. Infectious complications could vary between a simple local erythema at a puncture site that resolves easily with antibiotics to septicemia and death. As a corollary, this kind of complications continue to be among the most important causes of morbidity and mortality in end-stage renal disease patients receiving long-term hemodialysis. The cornerstone is prevention of infections. It is generally accepted that following simple measures during the intervention of graft insertion and consecutively in every hemodialysis session could consistently reduce the risk of infection.